2021
DOI: 10.3847/2515-5172/abf050
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Redshifts in the W-CDF-S and ELAIS-S1 Fields Based on Forced Photometry from 0.36 to 4.5 Microns

Abstract: The W-CDF-S and ELAIS-S1 fields will be two of the LSST Deep Drilling fields, but the availability of spectroscopic redshifts within these two fields is still limited on deg2 scales. To prepare for future science, we use EAZY to estimate photometric redshifts (photo-zs) in these two fields based on forced-photometry catalogs. Our photo-z catalog consists of ∼0.8 million sources covering 4.9 deg2 in W-CDF-S and ∼0.8 million sources covering 3.4 deg2 in ELAIS-S1, among which there are ∼0.6 (W-CDF-S) and ∼0.4 (EL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…The general reliability of the statistical uncertainties of our M å and SFR measurements ultimately arises from the reliability of the statistical uncertainties of the SEDs, which are justified indirectly and independently by the photo-z uncertainties in Zou et al (2021b). They showed that 78% of spec-zs reside in the 68% photo-z intervals.…”
Section: Validation Of M å and Sfr Uncertainties And Nominal Depth As...mentioning
confidence: 81%
See 4 more Smart Citations
“…The general reliability of the statistical uncertainties of our M å and SFR measurements ultimately arises from the reliability of the statistical uncertainties of the SEDs, which are justified indirectly and independently by the photo-z uncertainties in Zou et al (2021b). They showed that 78% of spec-zs reside in the 68% photo-z intervals.…”
Section: Validation Of M å and Sfr Uncertainties And Nominal Depth As...mentioning
confidence: 81%
“…Our redshifts are from Ni et al (2021a) and Zou et al (2021b). They compiled all the available spectroscopic redshifts (spec-zs) for 30,135 sources in W-CDF-S, and Zou et al (2021b) derived photo-zs for all the sources using EAZY (Brammer et al 2008).…”
Section: Redshiftmentioning
confidence: 99%
See 3 more Smart Citations